Effect of trace elements on the interface reactions between two lead-free solders and copper or nickel substrates - Soares, Delfim (2007)
Traditional Sn-Pb solder alloys are being replaced, because of environmental and health concerns about lead toxicity. Among some alternative alloy systems, the Sn-Zn and Sn-Cu base alloy systems have been studied and reveal promising properties. The reliability of a solder joint is affected by the solder/substrate interaction and the nature of the layers formed at the interface. The solder/substrate reactions, for Sn-Zn and Sn-Cu base solder alloys, were evaluated in what concerns the morphology and chemical composition of the interface layers. The effect of the addition of P, at low levels, on the chemical composition of the layers present at the interface was studied. The phases formed at the interface between the Cu or Ni substrate and a molten lead-free solder at 250º C, were studied for different stage times and alloy compositions. The melting temperatures, of the studied alloys, were determined by Differential Scanning Calorimetry (DSC). Identification of equilibrium phases formed at the interface layer, and the evaluation of their chemical composition were performed by Scanning Electron Microscopy (SEM/EDS). Different interface characteristics were obtained, namely for the alloys containing Zn. The obtained IML layer thickness was compared, for both types of alloy systems.